2013
DOI: 10.1002/prep.201200213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Homolog Doping on Surface Morphology and Mass‐Loss Rates from PETN Crystals: Studies using Atomic Force Microscope and Thermogravimetric Analysis

Abstract: Pentaerythritol tetranitrate (PETN) is an important energetic material, whose performance as a secondary explosive depends strongly on the density as well as flow porosity of powdered material, which in turn is governed by the size and surface properties of the PETN crystallite particles. Historically there has been evidence that the surface properties of PETN particles can be strongly influenced by the presence of homolog impurities of PETN, in particular, dipentaerythritol hexanitrate (diPEHN) and tripentaer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…PETN is a stable, powerful explosive with high brisance that is used throughout the U.S. military stockpile [1], commonly in devices such as EBW (exploding bridge wire) and EFI (exploding foil initiator) detonators. Because of this wide spread-usage, the stability properties and initiation behavior of PETN have been investigated over the past several decades [2,3,4,5,6,7]. However, there still exist important gaps in predicting its behavior in standard commercial detonators over long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…PETN is a stable, powerful explosive with high brisance that is used throughout the U.S. military stockpile [1], commonly in devices such as EBW (exploding bridge wire) and EFI (exploding foil initiator) detonators. Because of this wide spread-usage, the stability properties and initiation behavior of PETN have been investigated over the past several decades [2,3,4,5,6,7]. However, there still exist important gaps in predicting its behavior in standard commercial detonators over long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have shown that metal ions, as trace impurities, can change the crystal morphology, growth rate, and internal defects of explosives, thereby affecting their stability and, in particular, their thermal properties. [10][11][12] Xu et al 13 analyzed the influence of metal ion impurities on the crystallization and thermal properties of HMX and found that different types of metal ions have significant effects on the safety of explosives. Pitchimani et al 14 studied the morphology and activation energy of pure PETN crystals and PETN crystals doped with metal ion impurities.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction byproducts are easily obtained due to triethylboron reacting violently with water or oxidizer and through decomposition by heating during the synthesis procedure. Therefore, those byproducts served as impurities in synthesized triethylboron could affect the combustion performance and energy level of the ignition agents [14,15]. The detection and separation of impurities are crucial for the product quality of triethylboron, which is the key factor for ballistic performance, impact accuracy and storage safety.…”
Section: Introductionmentioning
confidence: 99%